2016
DOI: 10.1177/0884533615627268
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Time to Achieve the Steady State and Optimum Abbreviated Period to Estimate the Resting Energy Expenditure by Indirect Calorimetry in Healthy Young Adults

Abstract: Ten minutes can be used as an abbreviated alternative for IC measurements in healthy young adults, and values of the first 5-minute interval should be discarded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 17 publications
4
26
1
Order By: Relevance
“…Our results confirm these by Borges et al found the best abbreviated time for an IC measurement is 10 min, with the first 5 min being discarded (4). Specifically, they measured REE in 37 Brazilian college students (27 males and 12 females) for 30 min.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results confirm these by Borges et al found the best abbreviated time for an IC measurement is 10 min, with the first 5 min being discarded (4). Specifically, they measured REE in 37 Brazilian college students (27 males and 12 females) for 30 min.…”
Section: Discussionsupporting
confidence: 92%
“…The appropriate method for measuring REE in large observational trials is indirect calorimetry (IC). IC measures oxygen consumption (VO 2 ) and carbon dioxide production (VCO 2 ) and uses mathematically derived equations to estimate REE using a metabolic cart (1, 4). Traditionally, IC measurements require an individual lay supine in the postabsorptive state for 30–60 min while both VO 2 and VCO 2 are recorded (59).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the first RMR measurement, participants were given a standardised break in which they were instructed to take a walk over a standardised trajectory at their usual pace for 10 min to interrupt the steady state achieved in the first RMR measurement and to align pre-test conditions (i.e. no prior resting period) (18,19) for the measurements with the second device. The first 5 min of the data from both the measurements was discarded because the participants had to adapt their breathing while wearing the canopy hood (13,20) .…”
Section: Study Proceduresmentioning
confidence: 99%